Sinema Tari Sebuah Alternatif Solusi Produksi Tari Pada Masa Pandemi - Gita Kinanthi Purnama Asri Adinda (Jurnal Pendidikan Tari, 2021)
Dance cinema is a term used as a result of the work of Dance Production students at the STKIP PGRI Banjarmasin Dance Education Study Program during the pandemic. This qualitative research aims to describe the problems that arise in the Dance Production course and describe dance cinema as an alternative solution to dance production during the pandemic. The data were collected using interview, observation, documentation, and literature study techniques and analyzed to produce descriptive data. The results show that the pandemic period is a major problem and affects the learning system, the concept of dance production, and its distribution. Learning is usually done face-to-face and the results are presented in person, during a pandemic both cannot be done. The alternative solution chosen was to produce three dance cinemas with a blended learning process. The dance cinema entitled Tamula Gunung Hantanung, Manyingkai Pangambangan, and Darau Purun (Bersama Purun) is packaged in an online show. Shown live streaming on the YouTube channel Apm Production21 on 5,6, 7 March 2021 at 20.00 WITA. The highest number of dance cinema shows has reached 9000 views. This shows a positive response from the community towards the work. So that the choice of dance cinema as an alternative solution is considered effective and efficient during the pandemic, and can even be followed up in the short and long term.